A Market School: Pengelolaan Pendapatan dan Laporan Keuangan Sederhana untuk Pedagang Buah - Nikensari, Sri Indah; Nurjanah , Siti; Sari Komara, Lilis (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
This community development activity aims to provide understanding of material and earnings management techniques through lectures and simple financial application practices to improve the welfare of the parent Kramatjati market fruit traders in East Jakarta. This activity is part of activities carried out jointly with the theme